Developmental heterogeneity of embryonic neuroendocrine chromaffin cells and their maturation dynamics - Akkuratova, Natalia; Faure, Louis; Kameneva, Polina; Kastriti, Maria Eleni; Adameyko, Igor (Frontiers in Endocrinology, 2022)
During embryonic development, nerve-associated Schwann cell precursors (SCPs) give rise to chromaffin cells of the adrenal gland via the “bridge” transient stage, according to recent functional experiments and single cell data from humans and mice. However, currently existing data do not resolve the finest heterogeneity of developing chromaffin populations. Here we took advantage of deep SmartSeq2 transcriptomic sequencing to expand our collection of individual cells from the developing murine sympatho-adrenal anlage and uncover the microheterogeneity of embryonic chromaffin cells and their corresponding developmental paths. We discovered that SCPs on the splachnic nerve show a high degree of microheterogeneity corresponding to early biases towards either Schwann or chromaffin terminal fates. Furthermore, we found that a post-“bridge” population of developing chromaffin cells gives rise to persisting oxygen-sensing chromaffin cells and the two terminal populations (adrenergic and noradrenergic) via diverging differentiation paths. Taken together, we provide a thorough identification of novel markers of adrenergic and noradrenergic populations in developing adrenal glands and report novel differentiation paths leading to them.